Revolutionizing Petroleum Retail Outlet Operations: Artificial Intelligence for Improved Efficiency and Customer Experience - Jeenath Laila N; Mohamed Rizwan (International Journal of Medical Toxicology and Legal Medicine, 2024)
The petroleum retail outlet operations have become increasingly complex due to the growing demands of the industry. To keep up with the competition, retailers are seeking ways to optimize their operations, improve customer experience, and increase profitability. Artificial Intelligence (AI) has emerged as a powerful tool to help retailers achieve these objectives. In this paper, we explore the implementation of AI in petroleum retail outlet operations, including stock maintenance, sales delivery, Retail Outlet (RO) maintenance, amenities requirement, safety protocols, and customer retention. We discuss the benefits of AI in improving efficiency, reducing costs, and enhancing customer experience. We also highlight some of the challenges that retailers may face when implementing AI in their operations, including data quality, security, and ethical concerns. Overall, the implementation of AI in petroleum RO operations has the potential to revolutionize the industry and deliver significant benefits to both retailers and customers alike.